2015
DOI: 10.17718/tojde.46469
|View full text |Cite
|
Sign up to set email alerts
|

THE USE OF OPEN EDUCATIONAL RESOURCES IN ONLINE LEARNING: A Study of Students’ Perception

Abstract: Universitas Terbuka (UT) is Indonesia's higher education institution which implements distance education system. The term distance implies that learning is not performed faceto-face but there is geographically separation between students and teacher. Therefore, UT must provide many kinds of learning modes and learning support. To facilitate students in their learning process, UT provides an e-learning system named online tutorial. This tutorial is provided for all courses which are designed in 8 sessions of vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 8 publications
0
33
1
4
Order By: Relevance
“…The most important thing is how to integrate technology as a tool to support the learning process so that students can achieve their competencies better. The role of the teacher in this integration process becomes very important for the success of learning process (Algers & Silva-Fletcher, 2015, Atenas et al, 2015Harsasi, 2015;.…”
Section: Open Educational Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important thing is how to integrate technology as a tool to support the learning process so that students can achieve their competencies better. The role of the teacher in this integration process becomes very important for the success of learning process (Algers & Silva-Fletcher, 2015, Atenas et al, 2015Harsasi, 2015;.…”
Section: Open Educational Resourcesmentioning
confidence: 99%
“…Now, there are numerous learning sources to obtain to support the learning process in achieving specific competencies Krajcso, 2016;Piedra et al, 2015). Educators need to consider the necessity and the comfort of using this technology in managing the learning process in the new perspective using those learning sources (Harsasi, 2015;Obradović et al, 2016).…”
Section: Open Educational Resourcesmentioning
confidence: 99%
“…However, in reality, few of these programmes have provided specific evidence of impact, beyond learning skills, especially for marginalized students who may have distinct technological skills and habits due to their backgrounds and difficult working conditions. Prior investigations into OER in Indonesia offer technological proposals (Selviandro, Suryani, & Hasibuan, 2014) or evaluation of student perceptions (Harsasi, 2015), yet fail to suggest any improvement in their lives and livelihoods. (Cuban, 2014).…”
Section: Informal Digital Resources For Marginalized Populationsmentioning
confidence: 99%
“…From student perspectives, unsurprisingly, studies reported findings related to learning processes. For example, that students use OERs when they are enriching, of good quality, and have the freedom or choice to use OERs in a self-directed manner (Harsasi, 2015;Hatakka and Lagsten, 2012). Hatakka and Lagsten's (2012) reflection points out that OERs will positively impact on students from marginalized backgrounds if they transform relationships between teachers and students, which means that the pedagogical strategy is a primary mechanism that Scopus ICTD predicts the kind of transformation that an OER can contribute to.…”
Section: 2mentioning
confidence: 99%